Unreal Wages? Real Income and Economic Growth in England, 1260–1850. Issue 623 (16th May 2019) - Humphries, Jane; Weisdorf, Jacob
Abstract: Estimates of historical workers' annual incomes suffer from the fundamental problem that they are inferred from day wage rates without knowing how many days of work day-labourers undertook per year. We circumvent the problem by building an income series based on the payments made to workers employed by the year rather than by the day. Our data suggest that earlier annual income estimates based on day wages overestimate medieval labour incomes but underestimate labour incomes during the Industrial Revolution. Our revised estimates indicate that modern economic growth began more than two centuries earlier than commonly thought and was driven by an 'Industrious Revolution'. They also suggest that the current global downturn in labour's share is not exceptional but fits within the range of historical fluctuations.